Implementasi Prinsip-prinsip Dasar Manajemen Pendidikan Islam di SD IT Al-Akhyar Muara Bungo - Abni, Abni; Jamilus, Jamilus (Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to determine the extent to which Islamic education management principles are implemented in schools. This research uses a descriptive method which aims to describe or describe the phenomena that exist in schools. The results of this research can be concluded that the application of Islamic education management principles at SD IT Al-Akhyar Muara Bungo is quite good. Good in covering the principles of honesty, fairness, responsibility, sincerity and amar ma'ruf nahi munkar applied in carrying out activities at SD IT Al-Akhyar Muara Bungo.